Assessment of vertical pile reinforcement effect on behavior of foundations placed on Slopes: An experimental and numerical study - Sahar Memarian; Javad Ahadiyan; Hamid Reza Karimi (Ain Shams Engineering Journal, 2023)
In this research, the effect of using piles on the behavior of the foundation located on the slope has been studied experimentally and numerically. In the laboratory study, 12 models with a scale of 1:20, and in numerical analysis, 72 models in full-scale and laboratory-scale have been studied. The analyzed soil was made of clay. The results showed that reinforcing the slope with piles can significantly improve its behavior, so by increasing the ratio of pile length to foundation width from 1 to 4, an improvement of about 5 to 70% of the bearing capacity of the foundation systems was observed. In all scenarios, the ratio of failure settlement to the width of the foundation is 3 to 5 percent. Evaluations also showed that the use of piles with a length equal to the width of the foundation has no significant effect on the behavior of the foundation.